#### Answer

x=2.75

#### Work Step by Step

Simplifying
6x + 4 = 10x + -7
Reorder the terms:
4 + 6x = 10x + -7
Reorder the terms:
4 + 6x = -7 + 10x
Solving
4 + 6x = -7 + 10x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-10x' to each side of the equation.
4 + 6x + -10x = -7 + 10x + -10x
Combine like terms: 6x + -10x = -4x
4 + -4x = -7 + 10x + -10x
Combine like terms: 10x + -10x = 0
4 + -4x = -7 + 0
4 + -4x = -7
Add '-4' to each side of the equation.
4 + -4 + -4x = -7 + -4
Combine like terms: 4 + -4 = 0
0 + -4x = -7 + -4
-4x = -7 + -4
Combine like terms: -7 + -4 = -11
-4x = -11
Divide each side by '-4'.
x = 2.75
Simplifying
x = 2.75